2008
DOI: 10.1093/nar/gkn003
|View full text |Cite
|
Sign up to set email alerts
|

Functional relevance of novel p300-mediated lysine 314 and 315 acetylation of RelA/p65

Abstract: Nuclear factor kappaB (NF-κB) plays an important role in the transcriptional regulation of genes involved in immunity and cell survival. We show here in vitro and in vivo acetylation of RelA/p65 by p300 on lysine 314 and 315, two novel acetylation sites. Additionally, we confirmed the acetylation on lysine 310 shown previously. Genetic complementation of RelA/p65−/− cells with wild type and non-acetylatable mutants of RelA/p65 (K314R and K315R) revealed that neither shuttling, DNA binding nor the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 52 publications
4
104
0
Order By: Relevance
“…We did not detect recruitment of p65 acetylated at Lys-122/123, Lys-218, Lys-221, and Lys-310 to the IL-8, TNF, or IL-6 promoters (data not shown). Interestingly, acetylation of p65 at Lys-314/ 315 has been associated previously with a differential regulation of NFB target genes (43)(44)(45). In contrast to p65, however, Lys-314/315 ac-p65 occupancy at the IL-8 promoter was not dependent on IKK activity (Fig.…”
Section: Vorinostat-induced Il-8/cxcl8 Expression Is Dependent On Ikksupporting
confidence: 53%
“…We did not detect recruitment of p65 acetylated at Lys-122/123, Lys-218, Lys-221, and Lys-310 to the IL-8, TNF, or IL-6 promoters (data not shown). Interestingly, acetylation of p65 at Lys-314/ 315 has been associated previously with a differential regulation of NFB target genes (43)(44)(45). In contrast to p65, however, Lys-314/315 ac-p65 occupancy at the IL-8 promoter was not dependent on IKK activity (Fig.…”
Section: Vorinostat-induced Il-8/cxcl8 Expression Is Dependent On Ikksupporting
confidence: 53%
“…Posttranslational modifications of NF-κB, reviewed recently (7,15), include the acetylation of p65, which is inducibly modified at several sites, including K122, K123, K218, K221, K310, K314, and K315 under different conditions, with different effects on activity (16)(17)(18). In 293C6 cells, we observed the methylation of both K218 and K221 in response to activation of NF-κB.…”
Section: Discussionmentioning
confidence: 70%
“…For p53, K372 is methylated by the H3K4 methylase SET7/9, enhancing the subsequent acetylation of the same residue and in turn stabilizing p53 (24). In addition, the previously identified acetylated sites K314/K315 that are modified by CBP/p300 (18) were also recently identified as substrates for monomethylation catalyzed by the histone H3K4 methylase SET9 (25). The ways in which lysine methylation and acetylation are controlled to finely regulate NF-κB activity in normal and tumor cells, and the mechanisms that control the timing, location, intensity, residue specificity, and type of modification, are important issues for future research.…”
Section: Discussionmentioning
confidence: 95%
“…Although acetylation of the K218, K221, and K310 residues of p65 increases the transcriptional activity of NF-B, acetylation of the K122 and K123 residues reduces the transcriptional activity of NF-B by facilitating the nuclear export of p65 (25,26). In addition, acetylation at residues K314 and K315 of p65 has been shown to be important for NF-Bdependent transcription (36). In this study, we found that the acetylation of residues K314 and K315 of p65 was, at least in osteoclasts, of less importance for NF-B-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%